The green innovation effect of urban energy saving construction: A quasi-natural experiment from new energy demonstration city policy - Chen, Ming; Su, Yutong; Piao, Zaixu; Zhu, Jianhua; Yue, Xiaoguang (Journal of cleaner production, 2023)
Energy-saving construction has promoted the sustainable development of cities and is an important measure to achieve carbon neutrality and peak carbon. This paper uses the synthetic control method(SCM), propensity score matching difference-in-difference model(PSM-DID), spatial Durbin difference-in-difference model (SDM-DID) and other methods to explore the policy effect of energy-saving policy on the green innovation efficiency of Chinese cities based on the New Energy Demonstration City(NEDC) policy as a quasi-natural experiment. The paper has found that establishing NEDC can significantly improve the green innovation efficiency of pilot cities, and its positive impact continues to increase over time. The effect of energy-saving policy has regional heterogeneity, and NEDC can promote the improvement of urban green innovation efficiency more in eastern and central China. The results of PSM-DID further verify the robustness of the previous conclusion. The results of SDM-DID show that NEDC has a positive spatial spillover effect on the improvement of urban green innovation efficiency. NEDC policy can effectively promote the improvement of green innovation efficiency in neighboring cities of pilot cities. Mechanism analysis shows that NEDC affects urban green innovation efficiency by optimizing industrial structure, reducing resource dependence and gathering innovative elements. This paper enriches the research on the effect of urban energy-saving policies and provides policy references for improving urban green innovation capabilities. [Display omitted]